Making a Career Abroad—an Economic or Moral Issue? The Case of the Great Polish Emigration - Dobek, Rafał (Sensus Historiae, 2025)
Polish historiography, above all books by S. Kalembka, B. Konarska, Z. Sudolski or A. Witkowska as well as numerous biographies have so far only marginally touched upon the problems and dilemmas of emigrants in their professional careers. Meanwhile, Poles not only faced financial or organisational problems, but also complex moral dilemmas. This text shows, on the basis of selected cases, these dilemmas and the consequences that successful careers of emigrants entailed—like the withdrawal from Polish political life or the acceptance of new citizenship.